Refinements of Jensen's inequality for convex functions on the co-ordinates in a rectangle from the plane - Khan, Muhammad Adil; Ali, Tahir; Kilicman, Adem; Din, Qamar (Faculty of Sciences and Mathematics, University of Nis, 2016)
In this paper our aim is to give refinements of Jensen's type inequalities for the convex function defined on the co-ordinates of the bidimensional interval in the plane.